How Do the Players Play? A Post-Genomic Analysis Paradigm to Understand Aquatic Ecosystem Processes - Reid, Thomas; Bergsveinson, Jordyn (Frontiers in Molecular Biosciences, 2021)
Culture-independent sequencing methods – known collectively as meta-omics – have shed considerable light on the so-called “microbial dark matter” of the natural world, improving our understanding of phylogeny, the tree of life, and the vast functional diversity of microorganisms. This influx of sequence data has led to refined and reimagined hypotheses about the role and importance of microbial biomass, that paradoxically, sequencing approaches alone are unable to effectively test. Post-genomic approaches such as metabolomics are providing more sensitive and insightful data to unravel the fundamental operations and intricacies of microbial communities within aquatic systems. We assert that the implementation of integrated post-genomic approaches, specifically metabolomics and metatranscriptomics, is the new frontier of environmental microbiology and ecology, expanding conventional assessments towards a holistic systems biology understanding. Progressing beyond siloed phylogenetic assessments and/or cataloguing of metabolites, towards integrated analysis of expression (metatranscriptomics) and activity (metabolomics) is the most effective approach to provide true insight into microbial contributions towards local and global ecosystem functions. This data in turn creates opportunity for improved regulatory guidelines, biomarker discovery and better integration of modelling frameworks. To that end, critical aquatic environmental issues related to climate change, such as ocean warming and acidification, mitigation of contamination, and macro-organism health have reasonable opportunity of being addressed through such an integrative approach. Lastly, we argue that the “post-genomics” paradigm is well served to proactively address the systemic technical issues experienced throughout the genomics revolution and focus on collaborative assessment of field-wide experimental standards of sampling, bioinformatics and statistical treatments.